SIRT1 activation attenuates microglia-mediated synaptic engulfment in postoperative cognitive dysfunction - Sun, Yi; Wang, Yuzhu; Ye, Fan; Cui, Victoria; Lin, Dandan; Shi, Hui; Zhang, Yan; Wu, Anshi; Wei, Changwei (Frontiers in Aging Neuroscience, 2022)
Background Postoperative cognitive dysfunction (POCD) is a debilitating neurological complication in surgical patients. Current research has focused mainly on microglial activation, but less is known about the resultant neuronal synaptic changes. Recent studies have suggested that Sirtuin-1 (SIRT1) plays a critical role in several different neurological disorders via its involvement in microglial activation. In this study, we evaluate the effects of SIRT1 activation in a POCD mouse model. Materials and methods Exploratory laparotomy was performed in mice aged 12–14 months under sevoflurane anesthesia to establish our animal POCD model. Transcriptional changes in the hippocampus after anesthesia and surgery were evaluated by RNA sequencing. SIRT1 expression was verified by Western Blot. Mice were treated with SIRT1 agonist SRT1720 or vehicle after surgery. Changes in microglia morphology, microglial phagocytosis, presence of dystrophic neurites, and dendritic spine density were evaluated. Cognitive performance was evaluated using the Y maze and Morris water maze (MWM). Results Sirtuin-1 expression levels were downregulated in POCD. Exposure to anesthesia and surgery lead to alteration in microglia morphology, increased synaptic engulfment, dendritic spine loss, and cognitive deficits. These effects were alleviated by SRT1720 administration. Conclusion This study suggests an important neuroprotective role for SIRT1 in POCD pathogenesis. Increasing SIRT1 function represents a promising therapeutic strategy for prevention and treatment of POCD.